Wizja własnego życia i rytuały rodzinne wskazywane jako życiowe źródła wsparcia = Vision of your life and family rituals, support sources - Farnicka, Marzanna; Liberska, Hanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Rituals have been a part of our reality for a long time. As an individual subject of research they have been functioning since the second half of the nineteenth century. Contemporary studies concern the problem of changes connected with rituals, their importance, form and presence in the world today. The presented research is a part of this trend pointing to the need to create ritual experiences for people at junior high school age, as the elements controlling the overwhelming chaos which resulted from internal processes (creating identity) and the processes connected with the change of the environment (leaving primary school and entering junior high school).
Keywords: młodzież gimnazjalna; gimnazjaliści; rytuały; rodzina; tożsamość